Globalisasi sebagai Fenomen Kebudayaan - Mathias Daven; Maria Florentina Rumba; Aloysia Berlindis Lasar (Institut Filsafat dan Teknologi Kreatif Ledalero, 2023)
This paper emphasizes globalization as a cultural phenomenon, one that has repeatedly been neglectedacademically. It is better known as an economic phenomenon for its capitalism-related, production-orientedsystem and economic growth. Thus, the global economy is no longer affected by nations but the transnationalcompanies. However, the global economy primarily is a cultural phenomenon. Closely related to economicglobalization is the spread of the Western civilization model which includes Western cultural values, marketeconomy, production patterns, consumption patterns, and Western lifestyles. Apart from the fact that the model ofWestern civilization has its own charm, the dissemination of this model is also embodied by ideological conceit,namely an attitude that imposes its own cultural values on other parties. This development certainly triggers anextreme attitude that rejects universal values and retreats into one's own particular culture. To prevent the clashof civilizations, intercultural dialogue becomes notable. Globalization offers opportunities for cross-culturalencounters, and therefore the establishment of a “clash of cultures” must be regarded as a myth.Keywords: Globalization, economy, religion, dialogue, ambivalence